Severe hypertrophic cardiomyopathy in a patient with atypical Anderson-Fabry disease. (November 2017) - Masarone, Daniele; Duro, Giovanni; Dellegrottaglie, Santo; Colomba, Paolo; Rubino, Marta; Cirillo, Annapaola; Pisani, Antonio; Caiazza, Martina; Elliott, Perry Mark; Calabrò, Paolo; Pacileo, Giuseppe; Limongelli, Giuseppe
Aim: Anderson-Fabry disease (AFD) is a hereditary disorder caused by a deficiency in the lysosomal enzyme α-galactosidase A which causes dysfunctions in multiple organ systems. Cardiac manifestation includes left ventricular hypertrophy, thickening of the valves, conduction disturbances and in the late phase, extensive areas of myocardial fibrosis with increased risk of sudden cardiac death.Case example: A case of AFD with exclusive cardiac involvement is described. During follow-up, due to the high risk of life-threatening arrhythmic events, implantation of an implantable cardioverter defibrillator is performed.Conclusion: AFD patients with advanced cardiac disease might represent a subgroup of patients who may require an implantable cardioverter defibrillator for primary prevention of sudden cardiac death.